A Note on the Sri Lankan Experience in Poverty Reduction (The Pakistan Development Review, 2000)
‘Poverty’ is a complex, multifaceted and much investigated subject which has generated an colossal amount of literature. The situation in relation to Sri Lanka is no different—both in relation to the complexity of the subject and the investigation and literature it has generated. Within the international debates, Sri Lanka has been used extensively as a case study as in the early work on the basic needs and growth versus welfare debates, UNICEF’s work on Adjustment with a Human Face and more recently in the World Bank’s Voices of the Poor qualitative study. The domestic research and literature has been as prolific, the most recent group being the background material for the Framework on Poverty Reduction.1 This paper will not attempt to summarise the existing debates and literature or provide a comprehensive overview to poverty and its many facets in Sri Lanka. Instead it will briefly place Sri Lanka in the context of South Asia and look at the policy framework which brought about the present situation and the ongoing and envisaged policy changes. Finally it will highlight a few selected issues which are of growing interest and have received relatively less attention. A selected bibliography is provided at the end.